Can endometrial volume assessment predict the endometrial receptivity on the day of hCG trigger in patients of fresh IVF cycles: a prospective observational study - Singh, Neeta; Yadav, Anshu; Vanamail, Perumal; Kumar, Sunesh; K. Roy, Kallol; Sharma, Jai Bhagwan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Objective of present study was to evaluate the role of three dimensional (3D) endometrial volume measurement on the day of hCG trigger in predicting the endometrial receptivity. The present study is a prospective observational study conducted at assisted reproductive centre of a tertiary care hospital. Methods: Endometrial volume was evaluated by three-dimensional ultrasound in 90 patients undergoing first cycle of IVF on hCG trigger day and was correlated with endometrial receptivity. Results: Out of 90 patients studied 12 patients achieved pregnancy. A significant difference was found in mean endometrial volume on hCG trigger day among pregnant (5.33±2.14 cm3) women compared to non-pregnant women (4.17±1.72cm3). Using Receiver operating characteristics (ROC) analysis the cutoff value for endometrial volume on hCG trigger day was 3.50 cm3 corresponding to sensitivity 75% and specificity 37.2%. Conclusions: The endometrial volume on hCG trigger day was significantly higher in pregnant women as compared to non-pregnant.